2020
DOI: 10.1111/odi.13519
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent parathyroid hormone improves orthodontic retention via insulin‐like growth factor‐1

Abstract: Orthodontic retention is an indispensable part of a successful orthodontic treatment. However, relapse is commonly seen in clinic attributed to the physiologic response of supporting tissues to the exertion of force (Hirate, Yamaguchi, & Kasai, 2012). At the end of an orthodontic treatment, teeth are forced to their ideal positions while remodeling of periodontal tissues has not fully completed. Stresses and strains are still stored in the periodontal ligament (PDL) against orthodontic force, causing displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Results with the injection of bisphosphonates in vitro also suggested enhanced post-treatment stability [ 68 ]. Similar results have been suggested by Li et al [ 69 ] with intermittent parathyroid hormone administration, by Duliamy et al [ 70 ] with local injection with strodium, by Al-Fakhry et al [ 71 ] with injectable platelet rich fibrin (i-PRF) administration and by Zhao et al [ 40 ] with local OPG (osteoprotegerin) gene transfer to periodontal tissues. Ozturk et al [ 72 ] investigated the effect of photobiomodulation and high frequency mechanical vibration three-dimensionally and molecularly and found that both can support post-treatment retention.…”
Section: Discussionsupporting
confidence: 83%
“…Results with the injection of bisphosphonates in vitro also suggested enhanced post-treatment stability [ 68 ]. Similar results have been suggested by Li et al [ 69 ] with intermittent parathyroid hormone administration, by Duliamy et al [ 70 ] with local injection with strodium, by Al-Fakhry et al [ 71 ] with injectable platelet rich fibrin (i-PRF) administration and by Zhao et al [ 40 ] with local OPG (osteoprotegerin) gene transfer to periodontal tissues. Ozturk et al [ 72 ] investigated the effect of photobiomodulation and high frequency mechanical vibration three-dimensionally and molecularly and found that both can support post-treatment retention.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, this overexpression of IGF1 may be enhanced in maxillary alveolar bone when occlusal stimuli are associated with physical activity [ 106 ]. Of note, recent studies also showed that effects of intermittent parathyroid hormone (PTH) on the stability of orthodontic retention are improved by IGF1 [ 107 ].…”
Section: Gh/igf and Oral Tissue Engineeringmentioning
confidence: 99%
“…Bone remodeling necessary for orthodontic tooth movements involves active osteoclasts, which are positive for tartrate-resistant acid phosphatase (TRAP) activity and which may also be regulated by GH via GHR. Orthodontic tooth movements appeared to up-regulate GHR expression along rat alveolar bone, root surfaces, and PDL [ 104 , 107 ]. TRAP and GHR-positive cells were increased in the compression side along the alveolar bone, root surface, and in the PDL space in rats treated with orthodontic appliances for tooth movements [ 108 ].…”
Section: Gh/igf and Oral Tissue Engineeringmentioning
confidence: 99%
“…Parathyroid hormone acts directly on osteoblast and stimulates its differentiation and formation via STAT3/ β -catenin during OTM [ 89 91 ]. Li et al also observed upregulated osteogenic proteins OC, ALP, and IGF-1 in the gingival cervical fluid of mice after intermittent parathyroid hormone treatment [ 92 ]. There is substantial evidence to support the effect of estrogen deficient on bone mass and bone microarchitecture [ 93 95 ].…”
Section: Alveolar Bone Remodelingmentioning
confidence: 99%